ÙˆØ³ÙŠÙ„Ø© Ø§Ù„Ø£ÙˆØ±Ø§Ù‚ Ø§Ù„Ù…Ù…Ø²Ù‚Ø© ÙˆØªØ£Ø«ÙŠØ±Ù‡Ø§ Ø¹Ù„Ù‰ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø©: Ø¯Ø±Ø§Ø³Ø© ØªØ¬Ø±ÙŠØ¨ÙŠØ© ÙÙŠ Ù…Ø¹Ù‡Ø¯ ØªÙˆØ§Ù†ÙƒÙˆ Ù„Ù†ØªØ§Ùˆ Ø§Ù„Ø¹ØµØ±ÙŠ Ø§Ù„Ù…ØªØØ¯ÙŠ - Awalul Fajri (Lughawiyah: Journal of Arabic Education and Linguistics, 2020)
Ø§Ù„ØºØ±Ø¶Â  Ù„Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ù„Ù…Ø¹Ø±ÙØ© ØªØ£Ø«ÙŠØ± Ø§Ø³ØªØ¹Ù…Ø§Ù„Â  ÙˆØ³ÙŠÙ„Ø© Ø§Ù„Ø£ÙˆØ±Ø§Ù‚ Ø§Ù„Ù…Ù…Ø²Ù‚Ø© Ø¹Ù„Ù‰ Ù…Ù‡Ø§Ø±Ø© Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù†ØµÙˆØµ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙ‰ Ù…Ø¹Ù‡Ø¯ ØªÙˆØ§Ù†ÙƒÙˆ Ù„Ù†ØªØ§Ùˆ Ø§Ù„Ø¹ØµØ±ÙŠ Ø§Ù„Ù…ØªØØ¯ÙŠ Ø¨Ù…ØØ§Ø¸Ø© ØªØ§Ù†Ø© Ø¯Ø§ØªØ±.Ø£Ù…Ø§ Ù…Ù†Ù‡Ø¬ Â Ø§Ù„Ø¨ØØ« Ø§Ù„Ù…Ø³ØªØ¹Ù…Ù„ ÙÙ‡Ùˆ Ø§Ù„Ø¨ØØ« Ø´Ø¨Ù‡ Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠ Ù…Ø¹ Ø¹ÙŠÙ†Ø© Ø§Ù„Ø¨ØØ«Â  40Â  ØªÙ„Ù…ÙŠØ°Ø§ Ø§Ù„Ù…Ù‚Ø³Ù…ÙŠÙ† Ø¥Ù„Ù‰ Ø§Ù„ÙØ±Ù‚ØªÙŠÙ†ØŒ 20 ØªÙ„Ù…ÙŠØ°Ø§ Ù„Ù„ÙØ±Ù‚Ø© Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠØ©Â  ÙˆÂ  Ø§Ù„Ø¨Ø§Ù‚ÙŠØ© Ù…Ù†Ù‡Ù… Ù„Ù„ÙØ±Ù‚Ø© Ø§Ù„Ø¶Ø¨Ø·ÙŠØ©. Ø§Ø³ØªØ¹Ù…Ù„ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø·Ø±ÙŠÙ‚Ø© Ø§Ø®ØªØ¨Ø§Ø±ÙŠØ© Ù…Ø¹ ØªØÙ„ÙŠÙ„ Ø¥ØØµØ§Ø¦Ù‰ ÙÙ‰ ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª. Ø¯Ù„Øª Ù†ØªÙŠØ¬Ø© Ø§Ù„Ø¨ØØ« Ø£Ù† Ø§Ø³ØªØ¹Ù…Ø§Ù„ ÙˆØ³ÙŠÙ„Ø© Ø§Ù„Ø£ÙˆØ±Ø§Ù‚ Ø§Ù„Ù…Ù…Ø²Ù‚Ø© Ù„Ù‡ Ø¢Ø«Ø§Ø± Ø¹Ù„Ù‰ Ù…Ù‡Ø§Ø±Ø© Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù†ØµÙˆØµ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ¯Ù„Ù‘ Ø¹Ù„ÙŠÙ‡Ø§ ØªÙØ±ÙŠÙ‚ Ù†ØªÙŠØ¬Ø© Ø§Ù„ØªÙ„Ø§Ù…ÙŠØ° ÙÙ‰ Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù†ØµÙˆØµ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨ÙŠÙ† Ø§Ù„ÙØµÙ„ Ø§Ù„ØªØ¬Ø±ÙŠØ¨Ù‰ Ùˆ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø¶Ø¨Ø·ÙŠ. Ø£Ù† Ø§Ù„Ù†ØªÙŠØ¬Ø© Ø¨Ø§Ø®ØªØ¨Ø§Ø±-Øª (14,2) Ø£ÙƒØ¨Ø± Ù…Ù† Ù†ØªÙŠØ¬Ø©-Øª ÙÙ‰ Ø§Ù„Ø¬Ø¯ÙˆÙ„ (2,86) Ø¹Ù„Ù‰ Ø§Ù„Ø¯Ø±Ø¬Ø© 1%.The purpose of this study was to determine the effect of the use of snippets text media on Arabic reading proficiency at Integrated Modern Islamic Boarding School Tuanku Lintau, Tanah Datar regency. The research used a quasi-experimental method. The population was 40 students who were divided into an experimental group of 20 students and a control group of 20 students. Data collection technique was a test. Then, the data were analyzed using t-test. The result of this research described that the use of snippets text media has an effect on Arabic reading proficiency. This was indicated by the difference of studentsâ€™ learning outcomes between the experimental and control group. It was found that t-calculated 14.2 was higher than t-table 2, 86 atÂ  1% significance level.